227 Reduced drift rate: a biomarker of impaired information processing in functional movement disorders. Issue 6 (27th May 2022) - Sadnicka, Anna; Daum, Corinna; Meppelink, Anne-Marthe; Edwards, Mark; Manohar, Sanjay
Abstract : Recently the similarity of neuropsychiatric profiles across a range of functional syndromes has been high- lighted. This is suggestive of a common underlying mechanism with a theoretical deficit of information processing proposed. In this study, we took the temporal discrimination threshold, as a paradigm that can be used to model sensory processing in functional movement disorders. Our hypothesis was that we would be able to delineate markers of slowed information processing in this paradigm removed from the phenomenological presentation with a movement disorder. We recorded both response accuracy and reaction time in a two choice temporal resolution/discrimination task in 36 patients with functional movement disorders and 36 controls. We used a well-established model for decision-making (the drift diffusion model) to estimate mechanistic physiological dimensions of decision-making and sensory pro- cessing. This revealed pathologically reduced drift rate in the patient group, a parameter that quantifies the quality and rate of information accumulation within this sensory task (p=0.002). We discuss how the deficits we observed in patients with functional movement disorders are likely to stem from abnormal allocation of attention that impairs the quality of sensory information available. Within a predictive coding framework sensory information could be down-weighted in favour of predictions encoded by the prior. Our results therefore offer a parsimonious account for a range of experimental and clinical findings. asadnick@sgul.ac.uk